Oxygen uptake efficiency slope and peak oxygen consumption predict prognosis in children with tetralogy of Fallot. (July 2016) - Tsai, Yun-Jeng; Li, Min-Hui; Tsai, Wan-Jung; Tuan, Sheng-Hui; Liao, Tin-Yun; Lin, Ko-Long
Background: Oxygen uptake efficiency slope (OUES) and peak oxygen consumption (VO2 peak) are exercise parameters that can predict cardiac morbidity in patients with numerous heart diseases. But the predictive value in patients with tetralogy of Fallot is still undetermined, especially in children. We evaluated the prognostic value of OUES and VO2 peak in children with total repair of tetralogy of Fallot. Design: Retrospective cohort study. Methods: Forty tetralogy of Fallot patients younger than 12 years old were recruited. They underwent a cardiopulmonary exercise test during the follow-up period after total repair surgery. The results of the cardiopulmonary exercise test were used to predict the cardiac related hospitalization in the following two years after the test. Results: OUES normalized by body surface area (OUES/BSA) and the percentage of predicted VO2 peak appeared to be predictive for two-year cardiac related hospitalization. Receiver operating characteristic curve analysis demonstrated that the best threshold value for OUES/BSA was 1.029 (area under the curve = 0.70, p = 0.03), and for VO2 peak was 74% of age prediction (area under the curve = 0.72, p = 0.02). The aforementioned findings were confirmed by Kaplan–Meier plots and log-rank test. Conclusions: OUES/BSA and VO2 peak are useful predictors of cardiac-related hospitalization in children with total repair of tetralogy of Fallot.